A pilot study of operational tolerance with a regulatory T‐cell‐based cell therapy in living donor liver transplantation. Issue 2 (10th March 2016) - Todo, Satoru; Yamashita, Kenichiro; Goto, Ryoichi; Zaitsu, Masaaki; Nagatsu, Akihisa; Oura, Tetsu; Watanabe, Masaaki; Aoyagi, Takeshi; Suzuki, Tomomi; Shimamura, Tsuyoshi; Kamiyama, Toshiya; Sato, Norihiro; et al.
Abstract : Potent immunosuppressive drugs have significantly improved early patient survival after liver transplantation (LT). However, long‐term results remain unsatisfactory because of adverse events that are largely associated with lifelong immunosuppression. To solve this problem, different strategies have been undertaken to induce operational tolerance, for example, maintenance of normal graft function and histology without immunosuppressive therapy, but have achieved limited success. In this pilot study, we aimed to induce tolerance using a novel regulatory T‐cell‐based cell therapy in living donor LT. Adoptive transfer of an ex vivo ‐generated regulatory T‐cell‐enriched cell product was conducted in 10 consecutive adult patients early post‐LT. Cells were generated using a 2‐week coculture of recipient lymphocytes with irradiated donor cells in the presence of anti‐CD80/86 monoclonal antibodies. Immunosuppressive agents were tapered from 6 months, reduced every 3 months, and completely discontinued by 18 months. After the culture, the generated cells displayed cell‐number‐dependent donor‐specific inhibition in the mixed lymphocyte reaction. Infusion of these cells caused no significant adverse events. Currently, all patients are well with normal graft function and histology. Seven patients have completed successful weaning and cessation of immunosuppressive agents. At present, they have been drug free for 16‐33 months; 4 patients have been drug free for more than 24 months. The other 3 recipients with autoimmune liver diseases developed mild rejection during weaning and then resumed conventional low‐dose immunotherapy. Conclusions: A cell therapy using an ex vivo ‐generated regulatory T‐cell‐enriched cell product is safe and effective for drug minimization and operational tolerance induction in living donor liver recipients with nonimmunological liver diseases. (Hepatology 2016;64:632‐643)